Batman : the Dark Knight returns - Miller, Frank, 1957-; Janson, Klaus; Varley, Lynn; Costanza, John (2016)
The anniversary celebration of Frank Miller's epic interpretation of the Dark Knight's future continues with this new slipcase edition that reprints each issue of the original ark Knight returns miniseries in it's own hardcover volume, all in a beautifully designed slipcase. It is ten years after an aging Batman has retired, and Gotham City has sunk into decadence and lawlessness. Now, as his city needs him most, the Dark Knight returns in a blaze of glory. Joined by Carrie Kelly, a teenaged Robin, Batman takes to the streets to end the threat of the mutant gangs that have overrun the city. And after facing off against The Joker and Two-Face for the final time, Batman finds himself in mortal combat with his former ally, Superman, in a battle that only one will survive.
Batman. The Dark Knight returns. Book one -- Batman. Dark Knight triumphant. Book two -- Batman. Hunt the Dark Knight. Book three -- Batman. The Dark Knight falls.
Originally published in magazine form in Batman : Dark Knight 1-4.
In slip case.
Keywords: Comic books, strips, etc